Corporate Social Responsibility and Value of Manufacturing Firms in Nigeria’s Industrial Sector - William Smart Inyang; Efiong Eme Joel; Ije Ubana Ubi; Eyo Itam Eyo; Oboh John Ogenyi; Inyang Ochi Inyang (New Advances in Business, Management and Economics Vol. 4, 2025)
Background: Corporate performance is an indicator of the extent to which directors or managers of companies are carrying out their fiduciary duties of maximizing shareholders’ wealth while also engaging in other social activities. The global focus has now shifted to corporate social responsibility (CSR) practices, as the economic activities of corporate institutions significantly impact society and the environment. Purpose: The aim of this study is to determine how corporate social responsibility (CSR) practices can influence the corporate performances of listed firms in the industrial goods producing sector of Nigeria and other developing countries. Theoretical Framework: The enhancement of corporate value by CSR practices has become an interesting area of study for corporate managers and policymakers globally. The Stakeholder and Business Ethics theories were used for this study. However, it was primarily grounded in the Stakeholder Theory, proposed by Edward Freeman in 1984, to evaluate the influence of CSR on corporate value. Methodology: The study uses the causal comparative research design and we purposively select a sample of four industrial goods firms from Nigeria’s listed manufacturing enterprises as of 31st December 2021 based on their social responsibility relationships with society, employees and creditors. Nineteen years of secondary data were collected from the website of the Nigerian Exchange Group and the yearly financial reports of industrial goods-producing enterprises. These data have been analysed using the ordinary least squares panel data regression, fixed and random effects models, stationarity test, cross-section dependence test the Hausman test. Findings: The results show that corporate giving, employee welfare packages and creditor days have significant positive effects on return on assets (a proxy of corporate performance) suggesting that the threat to profit-maximization is not caused by CSR but by illegitimate use of CSR by rent-seeking corporate managers. Implications of this Research: The study helps in filling the gap in the literature and serves as a basis for the economic and social development of Nigeria, developed and other developing countries through a more legitimate CSR investment in corporate giving, employee welfare package and creditor settlement days. Moreover, this research established factors that may influence the corporate performances of Nigeria’s industrial goods-producing firms. The researchers used the outcomes of this research to conclude that CSR investments in corporate giving, employees’ welfare and settlement of creditors have significantly improved the corporate performances of listed industrial goods-producing firms in Nigeria. Value: The value of the study is that evidence of CSR success in the industrial goods manufacturing sector has for the first time been established using a time scope of 19 years and a firm-year-observations of 228. This study supports the claim that CSR is not a threat to profit maximization since it has a strong relationship with corporate value.